CYPRIA FILOXENIA - (:unkn) unknown (My University, 2026)
Non Governmental, Non profit organisation under the auspices of the Deputy Ministry of Tourism. The organisation aims to study, disseminate and promote examples of best practice in the Cyprus Hospitality Industry.